KEADAAN EKONOMI RUMAHTANGGA PETANI JAMBU METE DI KABUPATEN BUTON SULAWESI TENGGARA - Yusria, Wa Ode (Jurnal AGRISEP, 2010)
The research is aimed to investigate an economic welfare of cashew farmer household in Buton regency economically.  This study has been done in Buton regency.  Research area is selected purposively with 60 farmers selected as respondents with consideration whose can speaks Indonesian and willing for interviewed.  Data are analyzed using regression model approach.The result of this study showed that cashew farmer householsd in Buton regency economically were wealth and non poor farmers as indicated by good service ratio (GSR) of 0.99865.